DECISION OF THE DIRECTOR GENERAL OF TAXES ON THE 2013 CURRICULUM - Aqiq Zaman Rusnadi; Candra Ardi Sujono; M. Mahbubi (International Journal of Multidisciplinary Reseach, 2025)
The curriculum is an important component in the education system, including in Islamic religious education held in madrasahs. The decision of the Directorate General of Islamic Education of the Ministry of Religious Affairs to continue the implementation of the 2013 Curriculum (K-13) in the subject of Islamic Religious Education (PAI), although it was postponed nationally by the Ministry of Education and Culture, is a strategic step in improving the quality of religious education. This study aims to examine the implementation of this decision at Madrasah Aliyah Negeri (MAN) 2 Probolinggo as one of the madrasahs under the auspices of the Ministry of Religious Affairs. This study uses a qualitative approach with a case study method. Data were obtained through interviews, observations, and documentation of PAI teachers, madrasah principals, and students. The results of the study indicate that MAN 2 Probolinggo has consistently implemented the 2013 Curriculum in the subject of PAI, although it still faces several obstacles, such as limited learning media and the need for further training for teachers. However, in general, the implementation of this curriculum has a positive impact on improving the quality of learning and character building of students. This study recommends the need for ongoing mentoring and provision of supporting facilities so that the implementation of the 2013 Curriculum is increasingly optimal in madrasah.